2021
DOI: 10.1029/2020wr028741
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Modeling Drainage Network Contraction and Dry Down in Mediterranean Headwater Catchments

Abstract: Virtually all watercourses experience discontinuous flows along their drainage network. Nonpermanent streams can be observed not only in dry regions but also in most low-order channels of the network, representing more than 89% of the global river network (G. H.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 92 publications
6
34
0
Order By: Relevance
“…However, the influence of hydroclimatic drivers on the active fraction of the network is not fully understood. Notwithstanding the variability of across the study catchments (attributed to their geological diversity), our results confirm that the extent of active channel length is linked to the amount of excess precipitation in the contributing catchment, as previously proposed in the literature 12 , 31 . This suggests the emergence of distinctive ecohydrological patterns within different climatic regions of the world.…”
Section: Implications For Large-scale Studiessupporting
confidence: 90%
See 2 more Smart Citations
“…However, the influence of hydroclimatic drivers on the active fraction of the network is not fully understood. Notwithstanding the variability of across the study catchments (attributed to their geological diversity), our results confirm that the extent of active channel length is linked to the amount of excess precipitation in the contributing catchment, as previously proposed in the literature 12 , 31 . This suggests the emergence of distinctive ecohydrological patterns within different climatic regions of the world.…”
Section: Implications For Large-scale Studiessupporting
confidence: 90%
“…Conversely, in the wettest site (Coweeta, where P t − ET > 160mm/month), the mean network persistency approached unity and network dynamics are smoothed, with CV D → 0 . This result offers novel insight on the impact of climate on the active stream length variability 44 , and nicely complements existing modeling and empirical approaches for the characterization of the spatial patterns of flow persistency across a landscape 21,31,45 . Therefore, we believe that the proposed framework can provide useful insight into the impact of climate on the temporal changes of the active drainage density.…”
Section: Quantifying the Mean Active Drainage Density And Its Temporal Variationsmentioning
confidence: 57%
See 1 more Smart Citation
“…The surveys were carried out along a river reach some tens of meters long located approximately 550 m upstream of the outlet of the Upper Turbolo catchment [23] (Figure 1), Southern Italy. The catchment is 7 km 2 wide, with altitudes ranging from 183 m a.s.l.…”
Section: Study Sitementioning
confidence: 99%
“…The topic is experiencing a renewed interest of the scientific community owing to the influence of stream dynamics on hydrology, freshwater ecology, and biogeochemistry (e.g., [20][21][22]). In this context, the Mediterranean region is particularly challenging, owing to the enhanced variability of the active length in arid and semiarid regions [23,24]. Borg Galea et al [16] showed the usefulness of drones for monitoring intermittent Mediterranean rivers using RGB images.…”
Section: Introductionmentioning
confidence: 99%